Experience reports from active volunteer members in German right-to-die organisations through qualitative content analysis - Sandy Ohm; Claudia Bozzaro (BMC Medical Ethics)
Abstract Background Although not widely known to the general public, right-to-die organisations have been active in Germany since the 1980s, similar to Switzerland. Notably, there is often a lack of focus on the volunteer members of these organisations, despite their unique perspectives on the matter. Our study aims to thoroughly investigate the experiences of members in German right-to-die organisations and thereby make a significant contribution to the ongoing debate. Methods This project was implemented through qualitative interviews conducted with active volunteer members of German right-to-die organisations, followed by a qualitative structured content analysis based on Mayring’s approach. Using a coding evaluation method, relevant aspects were extracted from the data and on one hand assigned to predetermined categories, while one the other hand, new categories emerged organically from the material. Results After conducting 13 interviews, it became clear that, while some participants were deeply impacted by the dramatic nature of the illness-related circumstances surrounding certain assisted suicides, the majority do not find the work burdensome. Instead, they view it as highly fulfilling and rewarding. In particular, interacting with the relatives of those seeking assistance and with the individuals themselves is seen as especially enriching. Furthermore, participants frequently encounter significant ignorance from large segments of the medical community and law enforcement regarding current regulations, which can lead to complications during assisted suicides. Additionally, collaboration with care facilities and senior residences presents a considerable challenge for many members, often due to religious objections. Conclusion Our study of volunteer members of right-to-die organisations is, as far as we know, the first one with active volunteers of German right-to-die organisations. The interviews thus provide new and important insights into a lived practice that has been little studied. These insights must be incorporated into the current debate on the responsible establishment of the practice of assisted suicide.